PERANCANGAN ALAT PENEKAN DAN PENCETAK TERASI DENGAN KAPASITAS 50 KG PER JAM UNTUK UMKM TERASI DI TOBOALI - Prakoso, Bimo; Nabila Sari, Maulita; Alwi, Herwandi; Dwi Krishnaningsih, Shanty (Politeknik Manufaktur Negeri Bangka Belitung, 2025)
In the Toboali region, Mang Dodi's terasi UMKM company still uses traditional methods, which leads to a drawn-out manufacturing process, uneven product quality, and small production levels. Improved prawn paste printing techniques are therefore required in order to address the issue. To solve this problem, a faster mould and cutter should be designed utilising the VDI 2222 research approach. A methodical design process that allows for detailed process tracing is what distinguishes this approach. The two phases of the VDI 2222 method research process are concept formulation and planning. In the context of the integrated carrier system, the screw and printing system, and the cutter inside a single system, the study's findings help to clarify the alternative selection idea. This result reveals the ability to manufacture uniform goods, speed up processing times, and increase the quantity of products, all of which are commensurate with the research objectives.